Design and construction of a laboratory system for neuromuscular stimulation of the lower extremities during cycling - Popp, Matthias H (Division of Biomedical Engineering, 2018)
Functional Neuromuscular Stimulation (FNS) is a method by which paralyzed muscles are stimulated electrically in order to produce a useful movement. The design and testing of a laboratory system for the modulated control of the lower extremities during FNS-induced cycling on an exercising device (Paracycle) is described. The system hardware, which is designed around a standard IBM compatible Personal Computer, features six independent stimulation channels. Waveform characteristics such as pulse frequency, width and amplitude are defined as a function of the crank position of the Paracycle for each channel. An extensive software package allows programmability of the waveform parameters and supports the user in the definition of stimulation sequences. The effective performance of the complete FNS-controller/ Paracycle system has been demonstrated during a controlled case study with two paraplegic subjects.